The Capsid Protein of Rubella Virus Antagonizes RNA Interference in Mammalian Cells - Jiuyue Xu; Jing Kong; Bao Lyu; Xiaotong Wang; Qi Qian; Xi Zhou; Yang Qiu (Viruses, 2021)
Rubella virus (RuV) is the infectious agent of a series of birth defect diseases termed congenital rubella syndrome, which is a major public health concern all around the world. RNA interference (RNAi) is a crucial antiviral defense mechanism in eukaryotes, and numerous viruses have been found to encode viral suppressors of RNAi (VSRs) to evade antiviral RNAi response. However, there is little knowledge about whether and how RuV antagonizes RNAi. In this study, we identified that the RuV capsid protein is a potent VSR that can efficiently suppress shRNA- and siRNA-induced RNAi in mammalian cells. Moreover, the VSR activity of the RuV capsid is dependent on its dimerization and double-stranded RNA (dsRNA)-binding activity. In addition, ectopic expression of the RuV capsid can effectively rescue the replication defect of a VSR-deficient virus or replicon, implying that the RuV capsid can act as a VSR in the context of viral infection. Together, our findings uncover that RuV encodes a VSR to evade antiviral RNAi response, which expands our understanding of RuV–host interaction and sheds light on the potential therapeutic target against RuV.